Recommendations for Ethical Review of Veterinary Clinical Trials - Bertout, Jessica A.; Baneux, Philippe J. R.; Robertson-Plouch, Carol K. (Frontiers in Veterinary Science, 2021)
Ethical review of both human and animal research is critical to ensuring that studies are conducted with due regard to the welfare and safety of enrolled subjects and to the integrity of the data. However, differences exist in laws, policies, and best practices between human and animal studies. Ethical review is required for most human studies. While the laws and standards are clear for humans and for laboratory animals, the laws and standards for clinical research for client-owned animals are not as well-defined. Here, we discuss gaps in ethical review of clinical animal research in the United States of America and propose expanded functions for veterinary clinical studies committees as a solution.